Prolonged pain-to-balloon time still impairs midterm left ventricular function following STEMI - Dominik Felbel; Sabrina Fackler; Rachel Michalke; Michael Paukovitsch; Matthias Gröger; Mirjam Keßler; Nicoleta Nita; Yannick Teumer; Leonhard Schneider; Armin Imhof; Dominik Buckert; Wolfgang Rottbauer; et al. (BMC Cardiovascular Disorders, 2025)
Abstract Background ST-elevation myocardial infarction (STEMI) demands near-time reperfusion to reduce the risk of long-term heart failure. This study evaluates the proportion of impaired left ventricular ejection fraction (LVEF) following STEMI in the context of current healthcare settings at a tertiary care center equipped with the most advanced and up-to-date standards of care. Methods Patients experiencing STEMI as their first manifestation of coronary artery disease were analyzed, as these individuals had no prior experience with heart-related chest pain. LVEF was assessed by levocardiography at admission and semiautomatically using TOMTEC in patients with eligible full-cycle echocardiography of 2- and 4-chamber view available at discharge and 1-year follow-up (FU). Pain-to-balloon time was divided into quartiles (Q) [0-111, 112–159, 160–246 and 247–784 min]. Multiple logistic regression analysis identified independent predictors of reduced LVEF < 50% at 1-year FU. Results A total of 1,379 consecutive STEMI patients were reviewed from 2010 to 2017, with 130 meeting the inclusion criteria. Mean age was 63 ± 12 years, 75% were male, 14% had diabetes, 72% had arterial hypertension, and 56% had history of smoking. LVEF was reduced in 94% of patients at admission, 69% at discharge, and remained reduced in 45% at the 1-year follow-up. Anterior wall myocardial infarction (OR 3.2 [95%-CI 1.2–6.9], p = 0.018) and increasing pain-to-balloon time across quartiles (Q2: OR 15.7 [95%-CI 1.8–140.4], p = 0.014; Q4: OR 33.7 [3.4–278.7] p = 0.002) were independently associated with reduced LVEF at 1 year. Conclusion Despite optimal medical management and advanced healthcare structures, nearly half of patients with STEMI as their first presentation of coronary artery disease continue to exhibit reduced LVEF at 12-months. Anterior wall myocardial infarction and pain-to-balloon time exceeding 2 h remain independent predictors of left ventricular dysfunction. Further improvements in healthcare systems and public education are essential to reduce treatment delays and improve long-term outcomes.